Annealing of an AlN buffer layer in N2-CO for growth of a high-quality AlN film on sapphire - Miyake, Hideto (2016)
The annealing of an AlN buffer layer in a carbon-saturated N2–CO gas on a sapphire substrate was investigated. The crystal quality of the buffer layer was significantly improved by annealing at 1650–1700 °C. An AlN buffer layer with a thickness of 300 nm was grown by metalorganic vapor phase epitaxy (MOVPE), and was annealed at 1700 °C for 1 h. We fabricated a 2-µm-thick AlN layer on the annealed AlN buffer layer by MOVPE. The full widths at half maximum of the (0002)- and ($10\bar{1}2$)-plane X-ray rocking curves were 16 and 154 arcsec, respectively, and the threading dislocation density was 4.7 × 108 cm−2.